Comparative Study of Islamic Marriage Laws in Morocco and Algeria - Oyo Sunaryo Mukhlas; Basarudin, Basarudin (al-Afkar, Journal For Islamic Studies, 2024)
Morocco and Algeria are part of Muslim countries that use family law as a reference in dealing with the affairs of their people. Morocco is a kingdom located in the northwestern part of Africa; the northern part is bordered by the Mediterranean, the eastern part is bordered by Algeria, and the southeast and southern regions are bound by the French Sahara and Spain. In contrast, the Atlantic Ocean borders the western part. As for Algeria as a Muslim-majority country, it is not surprising that all forms of law regulation are based on Islam, which is also recognized as the official religion. The development of Islamic law in Algeria revolves more around Family Law. Regarding Islamic family law towards the two countries, namely Morocco and Algeria, the author needs to describe the Islamic family law model towards the countries of Morocco and Algeria. The goal is to provide an understanding of Islamic family law in the country. The approach used by the author is a comparative approach); in this study, it can be interpreted as an activity to compare the law of a country with the law of another country or the law of one time with a certain law of another time, in this case, Morocco and Algeria. The type of research the author uses for this discussion is qualitative, using the descriptive analysis method.